2023
DOI: 10.1001/jama.2022.21805
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Early High-Flow Nasal Oxygen vs Standard Oxygen Therapy on Length of Hospital Stay in Hospitalized Children With Acute Hypoxemic Respiratory Failure

Abstract: ImportanceNasal high-flow oxygen therapy in infants with bronchiolitis and hypoxia has been shown to reduce the requirement to escalate care. The efficacy of high-flow oxygen therapy in children aged 1 to 4 years with acute hypoxemic respiratory failure without bronchiolitis is unknown.ObjectiveTo determine the effect of early high-flow oxygen therapy vs standard oxygen therapy in children with acute hypoxemic respiratory failure.Design, Setting, and ParticipantsA multicenter, randomized clinical trial was con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
19
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 18 publications
2
19
0
1
Order By: Relevance
“…Third, a recent study of children with bronchiolitis in Canada reported an annual 7.2% increase in ICU admissions despite a stable hospitalization rate for bronchiolitis and a stable median length of stay of 3 days . This study, along with the study by Dr Franklin and colleagues, delineates the potential overuse of ICU resources for children and reemphasizes the confounding of clinical decision-making on primary outcomes in interventional trials.…”
mentioning
confidence: 70%
See 2 more Smart Citations
“…Third, a recent study of children with bronchiolitis in Canada reported an annual 7.2% increase in ICU admissions despite a stable hospitalization rate for bronchiolitis and a stable median length of stay of 3 days . This study, along with the study by Dr Franklin and colleagues, delineates the potential overuse of ICU resources for children and reemphasizes the confounding of clinical decision-making on primary outcomes in interventional trials.…”
mentioning
confidence: 70%
“…Second, a higher proportion of patients were transferred to the ICU in the high-flow oxygen therapy group vs the standard oxygen group (12.5% vs 6.9%) . However, the percentages of children who required noninvasive ventilation and invasive ventilation were similar, approximately 11% to 12%, in both groups.…”
mentioning
confidence: 93%
See 1 more Smart Citation
“…A greater proportion of children in the high flow oxygen group were admitted to the ICU (12.5% vs 6.9%) and did not tolerate the assigned treatment compared with children in the standard oxygen group. 21 The reasons of the observed increase in bronchiolitis ICU admission rates across the globe remain unclear, standing the stable hospital length of stay over most studies. The greater availability and use of NIV including HFNC without high quality evidence to guide its implementation, and the difficulty of the hospital team supervising HFNC in the ward may have at least contributed to this increase.…”
Section: F O R P U B L I C a T I O Nmentioning
confidence: 99%
“…In the Original Investigation titled “Effect of Early High-Flow Nasal Oxygen vs Standard Oxygen Therapy on Length of Hospital Stay in Hospitalized Children With Acute Hypoxemic Respiratory Failure: The PARIS-2 Randomized Clinical Trial,” published in the January 17, 2023, issue of JAMA , there was a percentage error. In Table 1, under the heading “Viral testing and data collected at randomization,” and under the category “Clinical diagnosis group,” in the last row under this category, “Other diagnosis group,” the data for the third column (“Standard oxygen”), should have been “15 (1.96)” instead of “15 (19.6).” This article was corrected online.…”
mentioning
confidence: 99%